Relationship Between Materialism and Inconspicuous Consumption: The Moderating Effect of Values - Martyna Płudowska; Andrzej E. Sękowski; Barbara Cichy-Jasiocha (Journal for Perspectives of Economic Political and Social Integration)
The last few decades have abounded in analyses devoted to materialism, its causes, consequences, and manifestations. Despite much evidence suggesting that materialism manifests itself as a propensity for conspicuous consumption, contemporary market trends show that it is necessary to re-examine the forms of consumption in which materialistic goals and values may transpire. In the present study, we investigated the relationship between materialism and inconspicuous consumption (IC), taking into account the moderating role of values. The study demonstrated that values played a moderating function in the relationship between materialism and IC: materialism turned out to be a positive predictor of IC among the participants who displayed a greater preference for security, conformity and tradition values. We also showed that the effect of materialism on IC was negative for individuals with a low preference for conservation values, but positive for those showing a high preference for this value category.